The Role of Plant-Based Diets in Preventing Chronic Diseases: Current Trends and Evidence - Elizawarda Elizawarda (Pt. Anagata Sembagi Education, 2024)
Chronic diseases such as type 2 diabetes mellitus, hypertension, heart disease and cancer are major challenges in global public health. Unhealthy diets, such as the consumption of foods high in saturated fat and low in fiber, contribute to the increasing prevalence of these diseases. Research shows that plant-based diets have significant potential in the prevention of these chronic diseases, thanks to their high fiber, antioxidant and phytonutrient content and low saturated fat. In addition to the health benefits, plant-based diets also support environmental sustainability by reducing greenhouse gas emissions, land use and natural resources compared to animal-based food production. While the adoption of plant-based diets is gaining popularity, challenges such as nutritional misconceptions, limited access to plant-based foods and cultural barriers need to be overcome. Stronger education and supportive public policies, such as subsidizing plant-based products and taxing animal products, are essential to expand their impact. Plant-based diets are not only a personal health solution, but also part of a global strategy to achieve the Sustainable Development Goals (SDGs), by reducing negative environmental impacts and increasing food security. This study aims to comprehensively explore the dynamics of adoption of plant-based diets as a chronic disease prevention strategy and its impact on health and the environment